Market-Based Corrective Actions - Bond, Philip; Goldstein, Itay; Prescott, Edward Simpson (Review of Financial Studies, 2010)
Many economic agents take corrective actions based on information inferred from market prices of firms’ securities. Examples include directors and activists intervening in the management of firms and bank supervisors taking actions to improve the health of financial institutions. We provide an equilibrium analysis of such situations in light of a key problem: if agents use market prices when deciding on corrective actions, prices adjust to reflect this use and potentially become less revealing. We show that market information and agents’ information are complementary, and discuss measures that can increase agents’ ability to learn from market prices.